Drivers Of Corporate Social Innovation: An Empirical Study Of Malaysian Public Listed Companies - Lim, Chia Yon (2022)
Business companies do not operate in a vacuum and are connected to the society. As such, business corporations are expected to provide solutions to some of the urgent social and environmental issues. Instead of remain stick in a “socially responsible” mindset, business corporations should view social issues at the core of the strategic consideration. Today, business companies are showing more interest in social innovation. By integrating RBV and dynamic capabilities perspective, this empirical study established a research framework to examine the influence of organizational resources and dynamic capabilities on CSI. A quantitative research was applied to understand the drivers of CSI and whether dynamic capabilities i.e. exploitation and exploration capabilities mediate the relationship between the organizational resources i.e. intellectual human capital, innovative culture and alliance networks and CSI.